MINAT INVESTOR MUDA UNTUK BERINVESTASI DI PASAR MODAL MELALUI TEKNOLOGI FINTECH - Tumewu, Ferdinand (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2019)
Investment is one of the factors that drive the economic growth of a region, which is beneficial to improve the economy, create equity, reduce poverty and increase regional and individual prosperity. The importance of this investment needs to be continued to be socialized especially to the younger generation and millennial generation so that in the future these young people can enjoy prosperity and help the regional and national economy. The problems faced include the lack of young people who invest and participate to invest, especially in the capital market. In addition, with the development of digital technology and industry 4.0 creating fintech technology to invest, but there are still less young generation to utilize this fintech technology to invest in the capital market. This study aims to examine the factors that influence the interests of young investors to invest in the capital market by utilizing fintech technology. Samples were taken from the younger generation in the city of Manado with a total sample of 100 respondents spread in the city of Manado. Data analysis using quantitative analysis by testing the hypothesis of the respondents' perceptions. The research results have implications for increasing the number of young people who are interested in investing in the capital market through fintech technology in North Sulawesi.Keywords: Â Intention, Young Investors, Investatio, Capital Market, Financial Technology